Amalgam and Composite Restoration in Posterior Teeth - Nomann, NA; Polan, MAA; Jan, CM; Rashid, F; Taleb, A (Bangladesh Journal of Dental Research & Education, 2013)
Basically most of the dentists choose amalgam for posterior restorations and they think amalgam is safe and poses no health risk to the patient. They also think that amalgam is the best material for posterior restoration as it can bear more masticatory stress, low price, easy to manipulate and also easy to handle/ place into the cavity. Moreover, their perception regarding amalgam is also very positive such as it is durable, the percentage of cusp fracture is less, no shrinkage and it has no toxic/harmful effect for oral health and general health also. But now a days controversy arises about this type of thinking in many clinical researches. Furthermore, composite became very popular to the dentist because of esthetic, two types of bonding (mechanical & chemical), less sound tooth structure have to remove, no harmful effect like mercury of amalgam, marginal leakage is less, cusp fracture is less, secondary caries detection easier than amalgam by radiograph, composite takes good polish, etc. But composite resins also have some disadvantages. This article has been prepared to give a picture on merits, demerits and different aspects of comparison on amalgam and composite restorative materials after reviewing different articles and publications. DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16593 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 30-35